Effect of Extracts and Bacteria from Korean Fermented Foods on the Control of Sesame Seed-Borne Fungal Diseases - Yong-Ki Kim (Research in Plant Disease, 2015)
In order to control seed-borne diseases, we obtained extracts from commercial fermented food products of Kimchi, Gochujang, Doenjang, Ganjang and Makgeolli and their suppressive effects against seed-borne diseases were studied. In addition, the suppressive effects of bacterial strains isolated from the fermented foods were screened in vitro and in vivo. Among fifty food extracts, twenty food-extracts suppressed more than 92% incidence of seedling rots in vitro and seven food extracts increased 58.3-66.8% of healthy seedling in the greenhouse. Among 218 isolates from the fermented foods, 29 isolates showing high antifungal activity against seven seed-borne fungal pathogens were selected. Among 29 isolates, 13 isolates significantly reduced seedling rot and increased healthy seedlings. Sixteen isolates with high antifungal activity and suppressive effect against sesame seedling rots were identified by 16S rRNA sequencing. Fourteen of sixteen isolates were identified as Bacillus spp. and the other two isolates from Makgeolli were identified as Saccharomyces cerevisiae. It was confirmed that B. amyloliquifaciens was majority in the effective bacterial population of Korean fermented foods. In addition, when the bioformulations of the two selected effective microorganisms, B. amyloliquifacien Gcj2-1 and B. amyloliquifacien Gcj3-1, were prepared in powder forms using bentonite, kaolin, talc and zeolite, talc- and kaolin-bioformulation showed high control efficacy against sesame seed-borne disease, followed by zeolite-bioformulation. Meanwhile control efficacy of each bentonite-bioformulation of B. amyloliquifacien Gcj2-1 and B. amyloliquifacien Gcj3-1 was lower than that of bacterial suspension of them. It was found that the selected effective microorganisms from Korean fermented foods were effective for controlling seed-borne diseases of sesame in vitro and in the greenhouse. We think that Korean fermented food extracts and useful microorganisms isolated from the extract can be used as bio-control agents for suppressing sesame seed-borne diseases based on above described results.